Snake Venom: Its Biochemical Components and Their Uses in Medicine - Umaru, Isaac John; Benjamin, Wisdom L. (African Journal of Biochemistry and Molecular Biology Research, 2025)
Snake venoms have components with diverse biological actions that are extensively studied to identify elements that may be useful in biomedical sciences. In the field of autoimmunity and rheumatology, various findings useful for the study of diseases and potential drug development have been reported. The study of disintegrins, proteins that block the action of integrins, has been useful for the development of antiplatelet agents and principles for the development of immunosuppressants and antineoplastic. Several proteins in snake venoms act on the coagulation cascade, activating factors that have allowed the development of tests for the study of coagulation, including Russell’s viper venom time, which is useful in the diagnosis of antiphospholipid syndrome. Neurotoxins with either pre- or postsynaptic effects have been used to study neurogenic synapses and neuromuscular plaques and the development of analgesics, muscle relaxants and drugs for neurodegenerative diseases. Various components act by inhibiting cells and proteins of the immune system, which will allow the development of anti-inflammatory and immunosuppressive drugs. This review summarizes the usefulness of the components of snake venoms in the fields of autoimmunity and rheumatology, which can serve as a basis for diverse translational research.